Insomnia in patients on hemodialysis for a short versus long duration - Tomita T; Yasui-Furukori N; Oka M; Shimizu T; Nagashima A; Mitsuhashi K; Saito H; Nakamura K (Neuropsychiatric Disease and Treatment)
Tetsu Tomita,1 Norio Yasui-Furukori,1 Masaki Oka,1 Takaaki Shimizu,2 Aya Nagashima,2 Kento Mitsuhashi,2 Hisao Saito,3 Kazuhiko Nakamura1 1Department of Neuropsychiatry, Graduate School of Medicine, 2School of Medicine, Hirosaki University, 3Department of Urology, Oyokyo Kidney Research Institute, Hirosaki, Japan Background: Many studies have investigated insomnia and the factors associated with this condition in hemodialysis (HD) patients, although the influence of HD duration has not been thoroughly investigated. In the present study, we investigated the factors, especially the duration of HD, associated with insomnia in HD patients.Patients and methods: A total of 138 patients undergoing HD were recruited, and the Japanese version of the Pittsburgh Sleep Quality Index (PSQI) was used to assess the quality of sleep. Subjects with a total PSQI score up to 4 and those with a score of at least 5 were identified as normal subjects and subjects with insomnia, respectively. Additionally, we assessed restless legs syndrome, depression using the Center for Epidemiologic Studies Depression Scale, and health-related quality of life (QOL) using the Short Form 8 Health Survey. We divided the subjects into two groups according to the median HD duration.Results: The prevalence rate of insomnia was 54.3% among all the subjects. Twenty-one subjects (15.2%) had depression, 26 (18.8%) had restless legs syndrome, and 75 (54.3%) had insomnia. The median HD duration was 4 years. The scores of components 1 and 4 of the PSQI, subjective sleep quality and habitual sleep efficiency, did not show a significant difference between the normal and insomnia groups. The score of component 7, daytime dysfunction, showed a significant difference between the short and long HD duration groups. In multiple regression analysis, the score of the Short Form 8 Health Survey showed a significant association with the PSQI score in the long HD duration group, but no variable showed a significant association in the short HD duration group.Conclusion: Patients with a longer duration of HD indicated that insomnia has an influence on their daily activities, with a significant association between insomnia and QOL. Greater attention should be paid to poor QOL and troubles in daily activities caused by insomnia in patients with a longer HD duration. Keywords: sleep disorders, kidney, quality of life, duration of hemodialysis